Combined effect of sedentary behavior and physical activity of different intensity on cardiovascular health - S. I. Loginov (Кардиоваскулярная терапия и профилактика)
Sedentary behavior (SB) and low (insufficient) physical activity (LPA) are two complementary negative factors affecting cardiovascular health. Most of the current studies are devoted to the study of SB and physical activity (PA) of different intensity separately, while their combined effect has not been studied enough. The purpose was to analyze the literature on the assessment of combined SB+PA effect of different intensity on the general and cardiovascular health of a person. When preparing the review, a search was made for publications in the MedLine, Cochrane, Scopus databases, as well as electronic resources e-library, CyberLeninka and libraries of physical culture and sports universities in Russia for 2002-2022.Issues related to various SB+PA combinations and their effects on general and cardiovascular health are considered and discussed. The facts of the favorable effect of switching sedentary behavior on the same time moderate-intensity PA are presented. The presented data indicate the need for further study, taking into account the mutual substitution of SB and FA of different intensity.